"It's not true": learning to learn from rejection. (15th December 2010) - Southwell, Mirjam; Thomas, Will
This paper explores the experience of two academics commissioned, by a public body engaged in policy formulation, to carry out research to inform the policy process. During the presentation of qualitative data to the public body, one representative exclaimed "it's not true!" The report was buried and we were rejected. We did not fully appreciate the implications of making recommendations from research that conflicted with existing policy interests. We suggest that the rejection of the report exposes the impact of lack of understanding of the political processes at play in policy-making. Meetings had been held and the use of qualitative methods had been agreed by all parties yet these meetings failed to prevent the rejection of the research. The paper concludes that the key challenge is in convincing policy makers of the validity and usefulness of qualitative evidence and offers tentative suggestions of how this task might be approached.